Ecosystem vs. community recovery 25 years after grass invasions and fire in a subtropical woodland. (20th October 2017) - D'Antonio, Carla M.; Yelenik, Stephanie G.; Mack, Michelle C.
Summary: Despite a large body of research documenting invasive plant impacts, few studies have followed individual invaded sites over decades to observe how they change, and none have contrasted how compositional impacts from invasion compare to ecosystem‐process impacts over a multi‐decadal time‐scale. Using direct measurements of plant density and composition and of ecosystems processes, we evaluate how ecosystem structure, above‐ground net primary production (ANPP), and above‐ground and soil nutrient pools compare over 25 years since fire and C4 grass invasions disrupted seasonally dry Hawaiian woodlands. We compare structure and function between primary woodland that has never burned and is largely native species‐dominated, with sites that had been the same woodland type but burned in alien‐grass‐fuelled fires in the 1970s and 1980s. The sites have not experienced fires since 1987. We report here that woody plant composition and structure continue to be dramatically changed by the initial invasions and fires that occurred 25 years ago and invaders continue to dominate in burned sites. This is reflected in continued low plant carbon pools in burned compared to unburned sites. Yet ANPP and N storage, which were dramatically lower in the initial decade after invasive‐grass fuelled fires, have increased and are now indistinguishable from values measured in intact woodlands. Soil carbon pools were resilient to both invasion and fire initially and over time. Above‐ground net primary production has recovered because of invasion of burned sites by a non‐native N‐fixing tree rather than because of recovery of native species. This invasive N‐fixing tree is unlikely to return C storage of the invaded sites to those of unburned woodland because of its tissue and growth characteristics and its interactions with invasive grasses. It does not facilitate native species but rather promotes a persistent invasive grass/N‐fixer savanna. Synthesis . We conclude that fire, an unusual disturbance in this system, has perpetuated the dominance of these sites by invasive species and that despite the dramatic recovery of above‐ground net primary production and N pools, the ecosystem continues to be in a distinctly different state than the pre‐fire, pre‐ Melinis community. Thus, despite the absence of further disturbance (fire), there is no evidence that succession towards the original ecosystem is occurring. The fact that N pools and above‐ground net primary production recover because of a new invader ( Morella faya ), highlights the unpredictability of ecosystem trajectories in the face of altered regional species pools. Abstract : We conclude that fire, an unusual disturbance in this system, has perpetuated the dominance of these sites by invasive species and that despite the dramatic recovery of above‐ground net primary production and N pools, the ecosystem continues to be in a distinctly different state that the pre‐fire, pre‐ Melinis community. Thus, despite the absence of further disturbance (fire), there is no evidence that succession towards the original ecosystem is occurring. The fact that N pools and above‐ground net primary production recover because of a new invader ( Morella faya ), highlights the unpredictability of ecosystem trajectories in the face of altered regional species pools.